Microcirculation in pregnancy - Abdo, I; George, R. B; Farrag, M; Černý, Vladimír; Lehmann, C (Physiological research, 2014)
The microcirculation, like all physiological systems undergoes modifications during the course of pregnancy. These changes aid the adaption to the new anatomical and physiological environment of pregnancy and ensure adequate oxygen supply to the fetus. Even though the microcirculation is believed to be involved in major pregnancy related pathologies, it remains poorly understood. The availability of safe and non-interventional technologies enabling scientists to study the intact microcirculation of the pregnant patient will hopefully expand our understanding. In this article we review the physiological changes occurring in the microcirculation during pregnancy and the role of the microcirculation in gestational related pathologies. We will also describe the available techniques for the measurement and evaluation of the microcirculation. Lastly we will highlight the possible fields in which these techniques could be utilized to help provide a clearer view of the microcirculation in the pregnant woman.
Keywords: dospělí; Animals; mikrocirkulace; Pregnancy Complications; lidé; Female; zvířata; Pregnancy; těhotenství; komplikace těhotenství; Adult; ženské pohlaví; Microcirculation; Humans